Older Humans and Their Dogs: Interspecies Companionship and Anticipating Loss - Bartram, Angela (Humanimalia, 2024)
Loneliness and a lack of socialization can have a deteriorating effect on life experience and health. Unfortunately, loneliness is an experience often felt by older people, and interspecies companionship can provide valuable and daily interaction that is positive for well-being. In the place of another human, a dog may inhabit a role as a provider of emotional support. In Judith Butler’s sense of performative identity, there is a becoming of that which we do. Using an approach of working with (rather than on) people, this informs sensitive and sympathetic methodologies for an analysis of the significance and benefit of interspecies companionship for older people in the initial stages of my artistic research project, Dogs and the Elderly. Made with participants of the Alzheimer’s Society’s “Memory Cafés” in Nottingham and Lincolnshire (UK), the project demonstrates how interspecies companionship can be valuable for supporting the emotional health and wellbeing of older people. This illustrated photo and text article discusses how the project’s older humans and their dogs inhabit a togetherness within supportive interspecies relationships in various ways, and how this contributes to their lived experience. It explores the stories of a group of people, living with or supporting others with early-stage Alzheimer’s, who speak to companionship with their dogs to articulate the significance of the relationship from their perspective.